2018
DOI: 10.1007/s11033-018-4234-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of curcumin in ameliorating AFB1-induced apoptosis via mitochondrial pathway in liver cells

Abstract: It is well documented that liver is the primary target organ of aflatoxin B (AFB) and curcumin proved to be effective against AFB-induced liver injury. In the present study, we investigated the preventive effects of curcumin against AFB-induced apoptosis through the molecular regulation of p53, caspase-3, Bax, caspase-9, Bcl-2 and cytochrome-C associated with mitochondrial pathway. Liver antioxidant levels were measured. The hallmarks of apoptosis were analysed by methyl green-pyronin-Y staining, transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…In support of this hypothesis, several studies have demonstrated the potential for antioxidants to lower the risk of hepatotoxicity caused by exposure to the AF [29,[36][37][38][39]. Moreover, many studies have reported the pivotal role of oxidative stress induced by AF in eliciting programmed cell death or apoptosis through mitochondrial signaling pathways [25,[40][41][42]. ROS induced mitochondrial damage is known to cause uncoupling of mitochondrial oxidative phosphorylation and the associated reduction in mitochondrial membrane potential following AFB1 administration in vivo and in vitro [25,33,35].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In support of this hypothesis, several studies have demonstrated the potential for antioxidants to lower the risk of hepatotoxicity caused by exposure to the AF [29,[36][37][38][39]. Moreover, many studies have reported the pivotal role of oxidative stress induced by AF in eliciting programmed cell death or apoptosis through mitochondrial signaling pathways [25,[40][41][42]. ROS induced mitochondrial damage is known to cause uncoupling of mitochondrial oxidative phosphorylation and the associated reduction in mitochondrial membrane potential following AFB1 administration in vivo and in vitro [25,33,35].…”
Section: Discussionmentioning
confidence: 91%
“…A likely explanation of this association is not yet identified, though consumption of AF-contaminated foods and feeds were reported to cause diverse degrees of liver injury comprising development of fatty cysts, fibrosis, and cirrhosis among humans and animals [23][24][25][26][27]. However, several lines of evidence support oxidative stress as a key factor in AF induced initiation and progression of liver cirrhosis [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were noted in previous studies. Researchers reported that AFB 1 exposure could result in apoptosis in the liver [45], BF [14], spleen [15], and thymus [46] of broilers, the mechanism associated with the mitochondrial pathway. However, the inclusion of PCs into AFB 1 contaminated diet prevented AFB 1 -induced up-regulation in Bax , caspase-3 , caspase-9 , p53 , and cytochrome-C and down-regulation in Bcl-2 mRNA expression levels as compared to the AFB 1 treated group.…”
Section: Discussionmentioning
confidence: 99%
“…108 Besides, curcumin can also ameliorate the aflatoxin B-induced apoptosis through the mitochondrial pathway in liver cells. 109 Furthermore, curcumin can not only mediate neuroprotection against mitochondrial complex I and II inhibitors by activating the nuclear factor erythroid 2-related factor 2 (Nrf2), but also mitigate the mitochondrial dysfunction by suppressing the ROS burst and the enhancing mitochondrial antioxidant gene expression. 110,111 In this regard, the mitochondrial function plays an imperative role in relieving depression related to curcumin treatment.…”
Section: Mitochondrial Function-related Antidepressant Mechanismsmentioning
confidence: 99%